ANALISIS PENTINGNYA LABELISASI HALAL TERHADAP PENINGKATAN PENJUALAN PRODUK INKUBATOR BISNIS UNIVERSITAS ISLAM AL-AZHAR MATARAM - Lale Ajeng Khalifatun Wardani; Aminy, Muhammad Habibullah (Fakultas Ekonomi dan Bisnis Universitas Islam Al-Azhar Mataram, 2023)
A halal certificate is an acknowledgment of the halalness of a product issued by a Halal Product Guarantee Agency based on a written halal fatwa issued by the Indonesian Ulema Council and a halal label is a sign of the halalness of a product. With the existence of a halal label on products, it will provide added value to production, distribution and consumption activities for Muslim consumers, whose market is very large in Indonesia. And consumer desires. This study used a qualitative method with a total number of ITe tenants at the Islamic University of Al-Azhar Mataram as many as 75 and the respondents who were taken were 10 tenants with various types of businesses such as coffee, wedang, chips, skin, pastries, special dishes, and so on. . The results of the study show that tenants who already have halal certification in their business get an increase in income compared to tenants who do not have halal certification in their business.